Inovasi Manajemen Bisnis Syariah pada Era Ekonomi Digital - Ibnu Safari Rahman (Annusfy : Journal of Multidisciplinary Research, 2026)
This study aims to analyze the implementation of Islamic business management principles in improving business performance and sustainability. Islamic business management is not only oriented toward material profit, but also emphasizes Islamic values such as justice, honesty, trustworthiness (amanah), and balance between worldly and spiritual interests.The research method used is a qualitative approach with a library research technique, which involves reviewing various relevant literature, books, and journals related to Islamic business management.The results of the study show that the implementation of Islamic principles in business management has a positive impact on improving business performance, particularly in terms of transparency, customer trust, and long-term business sustainability. In addition, Islamic business management is also able to create a more just economic system and avoid practices that harm one party, such as riba (usury), gharar (uncertainty), and maysir (gambling).Therefore, it can be concluded that the implementation of Islamic business management is highly relevant to be applied in facing modern economic challenges, especially in the current digital era.